The Post-Industrial Artisan Economy - Ponder,Caroline (2010)
Readers are presented with the idea that something significant and rather unusual is fomenting beneath the surface of the US economy regarding the renewed interest in all things handmade, handcrafted, or artisanally produced. That this interest is more than just a fad, and that its emergence is understandable in terms of theories of post-industrialism is what this essay aims to make clear. Discerning the economic geography of its emergence through empirical analysis is subsequently sought as well. Broader implications regarding the socio-economic impacts of an emergent post-industrial artisan economy are also considered.
Keywords: regulation approach; techno-economic paradigm; flexible specialization; small batch producers; post-industrial; artisan economy; artisan; Portland Oregon